Effect of plastic deformation on magnetic fields around fatigue crack tips of carbon tool steel (JIS, SKS93). (July 2016) - Kida, Katsuyuki; Ishida, Masayuki; Furuse, Mika; Mizobe, Koshiro; Santos, Edson Costa
Highlights: A scanning Hall probe microscope (SHPM) equipped with three GaAs films was developed. The magnetic field intensity decreases during crack growth. Polarization of the magnetic field occurs ahead of the fatigue cracks. The polarization moves while the crack grows. The magnetic fields move as the plastic area expands. Abstract: Small cracks form in steel and then grow to cause failure. It is important to observe the plastic deformation around cracks in order to understand the fatigue level of all kinds of steel components. However, at present, it is not easy to observe the plastic deformation at the crack tip during crack growth. In this study, in order to find a new, non-destructive testing method which is related to the cracks, we investigated the relationship between magnetic fields and plastic deformation around the crack tip. A scanning Hall probe microscope (SHPM) equipped with three-dimensional GaAs film equipment was used to observe the magnetic fields around a crack tip and the plastic deformation induced by Vickers indentations in tool steel specimens (SKS93, JIS B 4404: 2006, equivalent to AISI W4 tool steel). We found that the magnetic fields around the crack tip changed during the crack growth, and also that the decrease in the magnetic fields depends on the plastic deformation size.